Characterization of Hydraulic Spool Clamping Triggered by Solid Particles Based on Mechanical Model and Experiment Research - Qianpeng Chen; Min Liu; Hong Ji; Wenwei Chai; Changmin Luo (Applied Sciences)
Hydraulic spool valves may clamp under the action of sensitive particles when working in hydraulic oils that contain solid particles, which will then bring about a devastating detriment to the machines. According to the failure statistics of hydraulic systems organized by ISO, more than 80% of the operational failures of hydraulic systems are caused by fluid contamination, and particulate contamination is the most important factor causing spool valve stagnation. In this paper, we considered various factors, including the material, size, and concentration of particles and the spool postures, and built a systematic spool clamping mechanical model. A device was designed to measure the spool valve friction under the action of particles. The influence of particle material, concentration, and size on the friction force of spool valves was investigated. By experiments, we measured the spool clamping force under the action of each single factor and then fitted the datum quantity of spool clamping force and the empirical equation of pulsating quantity. The study results demonstrate three types of non-ideal postures of spools in a valve hole, which are off-center, tilting, and off-center with tilting. Those three postures can engender clamping risk zones with different ranges inside the clearance between spool valves, increasing the risk of spool clamping. The kind of particles is found to have a certain but limited impact on the spool clamping force. Usually, particles with a higher elastic modulus can trigger a larger spool clamping force, which is in line with the theoretical equation. Within a certain range, the probability density distribution of particle size tallies with the normal distribution function, where the “sensitive particles” take up 0.7–1 of the clearance between spool valves. A higher particle volume fraction in oils means a greater number of sensitive particles and a larger spool clamping force. For the particles of a similar size with the clearance between spool valves, when their volume concentration tops over the “sensitive concentration”, namely 5%, the risk of spool clamping rises in a drastic manner. This study provides a theoretical reference and an empirical equation for the mechanism of spool clamping under the action of particles, as well as a definite quantitative indicator for the prediction and estimation of spool clamping which is of positive significance for the study of the predictive maintenance of hydraulic equipment.